2022
DOI: 10.3390/vetsci9090480
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights Regarding the Role of Farm Animals in the Spread of Antimicrobial Resistance from a One Health Perspective

Abstract: Antimicrobial resistance (AMR) represents a global threat to both human and animal health and has received increasing attention over the years from different stakeholders. Certain AMR bacteria circulate between humans, animals, and the environment, while AMR genes can be found in all ecosystems. The aim of the present review was to provide an overview of antimicrobial use in food-producing animals and to document the current status of the role of farm animals in the spread of AMR to humans. The available body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 99 publications
0
16
0
1
Order By: Relevance
“…Many studies have focused on investigating the most ideal prevention strategy for PWD. In view of the increasing resistance to antibiotics and the limitation of their use in pig diets [19,20], pig nutrition plays a key role in future prevention strategies [55,56]. For example, previous studies reported the beneficial effects of adding vegetable oils to weaners' diets against pathogens, including E. coli, which can cause gastrointestinal diseases [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have focused on investigating the most ideal prevention strategy for PWD. In view of the increasing resistance to antibiotics and the limitation of their use in pig diets [19,20], pig nutrition plays a key role in future prevention strategies [55,56]. For example, previous studies reported the beneficial effects of adding vegetable oils to weaners' diets against pathogens, including E. coli, which can cause gastrointestinal diseases [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent regulations from 2022, the application of dietary ZnO in weaning feed has been forbidden in the European Union (EU) to reduce the negative environmental consequences of pig manure in agricultural soils [19]. Due to modern consumer demands and public health awareness, restrictions on the use of antibiotics as growth promoters in pig diets have also been proposed and applied [20]. Phytogenic feed additives (PFAs) have mainly been proposed as potential alternatives to in-feed antibiotics, based on their antibacterial activity against both Gram-negative and Gram-positive bacteria [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, veterinarians and farmers have undertaken a voluntary programme of reduction that has resulted in halving antibiotic use in food‐producing animals and reducing the use of the highest priority critically important antibiotics by nearly 80% since 2014 8 . During this time, further research has looked at the spread of resistance from livestock to humans, and a recent review has concluded that the contribution of farm animals to the spread of AMR to humans may not be as high as initial estimates, although this continues to be debated, as there are many unknowns and contradictory results 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 During this time, further research has looked at the spread of resistance from livestock to humans, and a recent review has concluded that the contribution of farm animals to the spread of AMR to humans may not be as high as initial estimates, although this continues to be debated, as there are many unknowns and contradictory results. 9 There is a wide-ranging body of work investigating veterinary surgeons' prescribing behaviours, as in the UK, all antibiotics need to be supplied by a veterinary surgeon. However, it can be argued that as antibiotics are often chosen and then administered by the farmer (including all relevant farm staff ) in the UK 10 and that farmers are the purchasers of the antibiotics, 11 'ultimately it is the farmer who is responsible for ensuring that animal medicines are used in a safe, responsible and effective way on farm'.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in an overview of AMU in food-producing animals and of the current state of knowledge regarding the role of farm animals in the spread of AMR in humans, actions taken in the livestock industry were presented, from a sustainable animal production perspective, in order to limit the spread of AMR bacteria and preserve the effectiveness of antimicrobials [ 18 ].…”
mentioning
confidence: 99%